PENGARUH MEDIA KATAM (KARTU KATA BERGAMBAR) TERHADAP KETERAMPILAN MENULIS PERMULAAN PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS I SDN 01 LUBAI ULU - Khoirun Nisa; Djunaidi; Hetilaniar (STKIP Subang, 2023)
The background of the problem in this study is that there are still many students' writing abilities which are still lacking, because educators at SD Negeri 01 Lubai Ulu still rarely use learning media which aims to develop students' initial writing skills. This study aims to determine the effect of the use of KATAM media on the initial writing ability of the first graders of SD Negeri 1 Lubai Ulu. The research method used is an experimental method using KATAM media (picture word cards). The subjects of this study were students in class I A and I B of SD Negeri 01 Lubai Ulu, which consisted of 49 students. Methods of data collection using tests and documentation. The test instrument was in the form of essay questions which totaled 10 questions to measure students' writing results. Data analysis technique using Independent Sample T-test. The results showed that the influence of ritatoon media can improve the learning outcomes of elementary school students in Indonesian language material which can be seen from the results of learning to test the hypothesis (Independent Sample T-Test) in the form of a significance value in this study, namely 0.000 <0.05, which means Ho is rejected Ha is accepted Keywords: KATAM Media, Student Beginning Writing